The study of antioxidant activities of piper sarmentosum and piper nigrum - Ibrahim, Maizatul Akma; Mohamad Asri, Nurul Aimi Amanina (Zibeline International Publishers, 2020)
Piper sarmentosum and Piper nigrum which belongs to family Piperaceae are well distributed in the tropical region including Malaysia. They are one of the medicinal plants which are well known for its health benefits to human. This study focused on determining the antioxidant activity of P. sarmentosum and P. nigrum leaves of ethanolic and aqueous extraction. For the extraction, different concentrations of ethanol and aqueous extracts were used. For the antioxidant activity, 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was conducted. The results showed that the scavenging activity of all extracts samples was in a concentration-dependent manner. High antioxidant activity of P. sarmentosum leaves was obtained by using ethanol extraction with 74% of inhibition, and IC50 value was 35.18 μg/mL. Meanwhile, P. nigrum leaves showed high antioxidant activity by using aqueous extraction with 64.68% of inhibition, and IC50 value was 79.89 μg/mL. It can be concluded that different extraction solvents used to give a different level of antioxidant activity of both P. sarmentosum and P. nigrum.